Rivals without a cause? Relative performance feedback creates destructive competition despite aligned incentives - Jan K. Woike; Sebastian Hafenbrädl (Journal of Behavioral Decision Making, 2020)
Whether people compete or cooperate with each other has consequences for their own performance and that of organizations. To explain why people compete or cooperate, previous research has focused on two main factors: situational outcome structures and personality types. Here, we propose that—above and beyond these two factors—situational cues, such as the format in which people receive feedback, strongly affect whether they act competitively, cooperatively, or individualistically. Results of a laboratory experiment support our theorizing: After receiving ranking feedback, both students and experienced managers treated group situations with cooperative outcome structures as competitive and were in consequence willing to forgo guaranteed financial gains to pursue a—financially irrelevant—better rank. Conversely, in dilemma situations, feedback based on the joint group outcome led to more cooperation than ranking feedback. Our study contributes to research on competition, cooperation, interdependence theory, forced ranking, and the design of information environments.
Keywords: 650; competition; cooperation; feedback; forced ranking; interdependence; public goods game; social comparison